In-water surface cleaning robot: concept, locomotion and stability. (1st January 2014) - Albitar, Houssam; Ananiev, Anani; Kalaykov, Ivan
This paper introduces a new concept of flexible crawling mechanism in the design of industrial in-water cleaning robot, which is evaluated from the viewpoint of work and operation on an underwater surface. It enables the scanning and cleaning process performed by water jets, while keeping stable robot position on the surface by its capacity to bear and compensate the jet reactions. Such robotic platform can be used for cleaning and maintenance of various underwater surfaces, including moving ships in the open sea. The designed robot implements its motions by contraction and expansion of legged mechanism using standard motors and suction cups technology. In this study we focus at the conditions for achieving enough adhesion for keeping continuous contact between the robot and the surface and robot stability in different situations for the basic locomotions.